Characteristics of the Risk of Production Development Caused Diseases of Sewers of JV "Tashteks" - Slavinskaya N. V.; Nuraliev F. N. (International Journal on Integrated Education, 2023)
Studies have established that the working conditions of sewing machine operators belong to the 3rd class of the 3rd degree of harmfulness; they can cause an occupational risk of developing diseases in working women. According to the “microclimate” factor, there is a risk of developing general somatic pathologies of the respiratory system, circulatory system, digestion, skin, visual and auditory analyzers, musculoskeletal, genitourinary systems, blood disorders during the cold season and the risk of injury to the fingers due to sweaty palms during the warm period. According to the “noise” factor, professionally caused 2nd degree of hearing loss is possible with 40 years of experience, and according to the “vibration” factor there is a risk of developing spasm of the blood vessels in the hands. According to the factor “severity of the labor process,” there is a likelihood of the formation of functional and pathological disorders of the muscles of the shoulder girdle. The intense nature of the work process of seamstresses-motorists indicates the likelihood of an occupational risk of developing neurotic disorders, hypertension and coronary heart disease.